Stakeholder Safety in Information Systems Research - Barbour, R.H. (Australasian Journal of Information Systems, 2006)
Information Communication Technology (ICT) researchers adapt and use tools from reference and cognate disciplines. This application of existing tools outside the context of their development has implications beyond the immediate problem context. ICT researchers have access to a wide variety of data sources including newer ones, such as the Internet, that may bring unexpected outcomes. ICT research can impact on researchers, their institutions and the researched in unexpected ways. People so affected are the stakeholders in ICT research activities. Reputations, welfare and property may be put at risk by unplanned events described in this paper. Legal aspects of ICT research are broadly identified and linked to the tort of negligence. The Social Research Association’s Code for researcher safety is described and its application extended to include the Internet as a potential data source. A common set of underlying ethical principles is identified suggesting that the ICT researcher can refine particular research protocols for specific social contexts.